Định giá và bảo hộ quyền chọn với chi phí thanh khoản - Nguyễn Hữu, Thái (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
In this note, we revise some pricing PDEs that arise from problems of option pricing and hedging under liquidity costs or transaction costs, using an appropriately adjusted volatility for the classical pricing Black-Scholes PDEs. We discuss the asymptotic behavior of the hedging error of the Leland strategy under liquidity costs under the presence of liquidity costs in the CJP model as proposed by Cetin et al. (2006). The author obtains that for a continuous supply curve, while intermediate liquidity costs for the Leland strategy can be omitted, the initial liquidity cost plays an essential role that should be considered in option pricing. Super-replication can be obtained